CX3CL1 induces cell migration and invasion through ICAM‐1 expression in oral squamous cell carcinoma cells - Wu, Chia‐Yu; Peng, Pei‐Wen; Renn, Ting‐Yi; Lee, Chia‐Jung; Chang, Tsung‐Ming; Wei, Augusta I‐Chin; Liu, Ju‐Fang (Journal of Cellular and Molecular Medicine, 2023)
Human oral squamous cell carcinoma (OSCC) has been associated with a relatively low survival rate over the years and is characterized by a poor prognosis. C‐X3‐C motif chemokine ligand 1 (CX3CL1) has been involved in advanced migratory cells. Overexpressed CX3CL1 promotes several cellular responses related to cancer metastasis, including cell movement, migration and invasion in tumour cells. However, CX3CL1 controls the migration ability, and its molecular mechanism in OSCC remains unknown. The present study confirmed that CX3CL1 increased cell movement, migration and invasion. The CX3CL1‐induced cell motility is upregulated through intercellular adhesion molecule‐1 (ICAM‐1) expression in OSCC cells. These effects were significantly suppressed when OSCC cells were pre‐treated with CX3CR1 monoclonal antibody (mAb) and small‐interfering RNA (siRNA). The CX3CL1‐CX3CR1 axis activates promoted PLCβ/PKCα/c‐Src phosphorylation. Furthermore, CX3CL1 enhanced activator protein‐1 (AP‐1) activity. The CX3CR1 mAb and PLCβ, PKCα, c‐Src inhibitors reduced CX3CL1‐induced c‐Jun phosphorylation, c‐Jun translocation into the nucleus and c‐Jun binding to the ICAM‐1 promoter. The present results reveal that CX3CL1 induces the migration of OSCC cells by promoting ICAM‐1 expression through the CX3CR1 and the PLCβ/PKCα/c‐Src signal pathway, suggesting that CX3CL1‐CX3CR1‐mediated signalling is correlated with tumour motility and appealed to be a precursor for prognosis in human OSCC.